Analysis of factors influencing re-visit intention of diabetes mellitus patients at dr. Pirngadi General Hospital - Loren, Jeff; Zannah, Rafika; Hutauruk, Magdalena Julianni; Kuswani, Lili; Delfian, Taufik; Haryadi, Haryadi; Lumban Tobing, Andrico Napolin; Sopacua, Erwin; Arviandi, Rizki; Cisca, Anita Merry; Nadapdap, Faskanita Maristella; Putra, Kriswandy (Buletin Kedokteran & Kesehatan Prima, 2025)
Diabetes mellitus is a non-communicable disease that requires a long treatment so that patients have to take medication or visit the hospital more often, interest in repeat visits is a behavior that appears in response to objects that indicate a customer's desire to make a repeat purchase. The aim of the study was to find out whether the factors that determine interest in returning to diabetes mellitus patients at Pirngadi Hospital in Medan City in 2023. The research method uses a correlative descriptive design with a cross-sectional approach. The results showed that most of the respondents were male, namely 23 (51.1%), the education level of respondents who were high and medium had the same proportion, namely 18 (40%), the employment status of respondents was 30 (66.7%) working. Quality of service as many as 33 (73.3%) and as many as 28 (62.2%) families get high support. The results of the statistical chi-square test found that there was no significant relationship between gender and intention to revisit (p=0.155), there was no relationship between education and intention to revisit (p=0.371), there was no relationship between work and intention to revisit (p=0.828), there is a relationship between quality of service and interest in repeat visits (p=0.000). There is no relationship between family support and interest in repeat visits (p=0.000). This research is expected to be an evaluation material in improving health services related to the determinants of interest in repeat visits of patients with diabetes mellitus.